2009
DOI: 10.1016/j.arcmed.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of a Vaccine Against Novel Influenza A (H1N1) Virus Among Health Care Workers in Two Major Cities in Mexico

Abstract: Background and Aims-Further cases of novel influenza A (H1N1) outbreak are expected in the coming months. Vaccination has been proven to be essential to control a pandemic of influenza; therefore, considerable efforts and resources have been devoted to develop a vaccine against the influenza A (H1N1) virus. With the current availability of the vaccine, it will be important to immunize as many people as possible. However, previous data with seasonal influenza vaccines have shown that there are multiple barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
58
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 6 publications
8
58
0
Order By: Relevance
“…In this study, the unreliability and side effects were the main reasons for unwillingness. That was similar to other surveys, apart from the study of Jaramillo AE et al [3,[14][15][16]. One of an interesting results of our study was the effect of the media on the attitudes of students.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In this study, the unreliability and side effects were the main reasons for unwillingness. That was similar to other surveys, apart from the study of Jaramillo AE et al [3,[14][15][16]. One of an interesting results of our study was the effect of the media on the attitudes of students.…”
Section: Discussionsupporting
confidence: 77%
“…The low level of knowledge towards H1N1 of the health group students who shall be a reliable source of knowledge for the public derives a necessity of education and training. The willingness to receive the Influenza A(H1N1) vaccine was quite low in our study like other studies in Turkey, although lower than studies in other countries, especially for the health group compared to international health proffesionals [3,5,10,[14][15][16]. Additionally, a considerable proportion of the study group was undecided.…”
Section: Discussionmentioning
confidence: 53%
“…Among the HCPs we surveyed, the willingness to be vaccinated against pH1N1was high. Similar acceptance rates for vaccination have been reported in other studies among the general population (Mexico 80% [28], Canada 69% [29] and 75% [30], and 89% in Kenya [31]). However, our results are markedly different from those in other studies that have reported a low willingness to be vaccinated in HCPs [13][14][15][32][33][34][35].…”
Section: Discussionsupporting
confidence: 72%
“…Our overall findings pertaining to why some parents refuse to have their children vaccinated are in line with those of previous studies that have identified misperceptions regarding disease susceptibility and vaccine efficacy and concerns about safety. 15,16 Moreover, lack of trust in vaccines and in those who deliver them (e.g. health-care providers, governments and international agencies) has been identified as an important hindrance to routine OPV immunization and polio elimination.…”
Section: Discussionmentioning
confidence: 99%